1989
DOI: 10.1002/jcp.1041410224
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epidermal growth factor/transforming growth factor‐α–stimulated cell growth by a synthetic peptide

Abstract: Estrogen-stimulated growth of the human mammary adenocarcinoma cell line MCF-7 is significantly inhibited by monoclonal antibodies to the epidermal growth factor (EGF) receptor that act as antagonists of EGF's mitogenic events by competing for high-affinity EGF receptor binding sites. These antibodies likewise inhibit the EGF or transforming growth factor-alpha (TGF-alpha)-stimulated growth of these MCF-7 cells. An analogous pattern of specific EGF or TGF-alpha growth inhibitory activity was obtained using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…These conclusions are in agreement with previous data showing that either neutralizing anti-TGFa antibodies and/or blocking anti-EGFR antibodies are able to produce a 50-75% inhibition of the E2-stimulated growth of MCF-7 cells that have been propagated under either ADG or AIG conditions (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991). The specificity of these antibodies on MCF-'7 cells was confirmed by their ability to inhibit either EGF-or TGFa-stimulated ADG (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991). In addition to these results, the basal or E2-stimulated clonogenicity of some primary human breast tumor cells in soft agar can be inhibited by either anti-TGFa neutralizing antibodies or by anti-EGFR-blocking antibodies (Ahmed et al, 1991).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These conclusions are in agreement with previous data showing that either neutralizing anti-TGFa antibodies and/or blocking anti-EGFR antibodies are able to produce a 50-75% inhibition of the E2-stimulated growth of MCF-7 cells that have been propagated under either ADG or AIG conditions (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991). The specificity of these antibodies on MCF-'7 cells was confirmed by their ability to inhibit either EGF-or TGFa-stimulated ADG (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991). In addition to these results, the basal or E2-stimulated clonogenicity of some primary human breast tumor cells in soft agar can be inhibited by either anti-TGFa neutralizing antibodies or by anti-EGFR-blocking antibodies (Ahmed et al, 1991).…”
Section: Resultssupporting
confidence: 94%
“…In addition, the data also show that treatment with the blocking anti-EGFR 528 monoclonal antibody or expression of a TGFa antisense mRNA can partially or totally inhibit the E2-stimulated ADG or AIG of MCF-7 cells, thereby substantiating the possibility that TGFa is capable of acting as one intermediary for mediating part of the biological effects of estrogens in ER-positive, estrogenresponsive human breast cancer cells (Bates et al, 1988). These conclusions are in agreement with previous data showing that either neutralizing anti-TGFa antibodies and/or blocking anti-EGFR antibodies are able to produce a 50-75% inhibition of the E2-stimulated growth of MCF-7 cells that have been propagated under either ADG or AIG conditions (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991). The specificity of these antibodies on MCF-'7 cells was confirmed by their ability to inhibit either EGF-or TGFa-stimulated ADG (Bates et al, 1988;Eppstein et al, 1989;Manni et al, 1991).…”
Section: Resultssupporting
confidence: 89%
“…Laminin can also stimulate DNA synthesis and cell growth in cells possessing functional EGF receptors (Panayotou et al, 1989), and anti-laminin receptor antibodies can inhibit EGF-stimulated proliferation (Eppstein et al, 1989), suggesting a relationship between laminin-and EGF receptor-mediated events. Given that the EGF receptor is a ligand-stimulated tyrosine kinase (Carpenter and Cohen, 1990;Gill et al, 1987), it is noteworthy that the clustering of the PI integrin, a component of several laminin receptors (Hynes, 1992), can also induce tyrosine phosphorylation (Kornberg et al, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Received October 10,1994; accepted February 6,1995 (Hynes, 1992;Kramer et al, 1990). These binding proteins can recognize specific functional regions on laminin; i.e., their interaction is defined by distinct domains (Beck et al, 1990;Hynes, 1992).Of particular interest is the observation that one laminin domaidfragment (and related peptides) containing an epidermal growth factor (EGF)-like motif can influence the attachment (Terranova et al, 1983) and EGF-stimulated mitogenesis (Eppstein et al, 1989) of several breast cancer cell lines. This laminin fragment can also stimulate DNA synthesis in Swiss 3T3 fibroblasts possessing EGF receptors, but has less of an effect on a mutant cell line (NR-6) lacking the EGF receptor (Panayotou et al, 1989).…”
mentioning
confidence: 98%
“…Previous studies have shown that synthetic peptide fragments of EGF (13)(14)(15)(16) and TGF-␣ (17)(18)(19) bind only weakly to EGF-R, nevertheless, only peptides corresponding to the B-loop segment of EGF have been consistently shown to bind to the EGF-R and invoke a weak mitogenic response. While low activity of synthetic peptide fragments may reflect the complex interaction of the ligand with EGF-R, it may also be due to failure of these peptides to adopt a conformation similar to that of the native ligand.…”
mentioning
confidence: 99%